Mother's Knowledge and Attitude Regarding Speech Delay Prevention in Children: A Cross-sectional Study in Pantai Labu Health Center of Deli Serdang Regency - Lase, Hidawati; Herawati; Barus, Helpinta; Siregar, Debi Novita (Al-Hijrah Indonesia, 2024)
Background: The term speech delay is a disorder of speech delay which is classified as an expressive language disorder or with difficulty expressing, which occurs in early childhood. The lack of communication time between young children and their parents or peers can affect their language skills. Objective: To find out whether there is a relationship between mother's knowledge and attitudes regarding preventing speech delay in children aged 1-3 years. Method: This research uses descriptive analytical research with a cross-sectional research design. The population used was all mothers who had children aged 1-3 years with a total sample of 111 people, and the sampling technique was the Non- Probability Sampling technique. Results: The results of the Chi-square test statistic showed a p-value = 0.00. With a 95% confidence level ∝ = 0.05. This means that there is a relationship between maternal knowledge and the prevention of speech delay in children aged 1-3 years in the Pantai Labu Health Center, Deli Serdang Regency. The statistical test results of the Chi-square test showed a p-value = 0.00. With a 95% confidence level ∝ = 0.05. This means that there is a relationship between the mother's attitude and the prevention of speech delay in children aged 1-3 years in the Pantai Labu Health Center. Conclusion: It is hoped to provide support and information to mothers to find out their child's language development and detect early if there are problems with their language development (speech delay).